PERKEMBANGAN TEKNOLOGI DALAM INDUSTRI MEDIA - Machmud, Muslimin (Jurnal Teknik Industri, 2011)
Globalization is happening at the present time, have an impact on all aspects of human life, including how humans acquire and convey information. As the world becomes cosmopolitan, so as to create cultural uniformity that makes human communication affect each other even though the place is very far apart. One of the demands of globalization is the information accessible to the whole society. Thus, the existing media industry should be able to meet that demand. One effort that needs to be done by the media industry is to make the adjustments to the advancement of existing technology. The globalization of information that played by the media industry has put developing countries as a share of the world information society that requires the establishment of regulation and use of information technology in each country in response to developments in both regional and international levels. Activities use of information technology should be developed without compromising the rights of audience in a fair manner, so that the violations related to the use of information technology can be avoided through the application of uniform principles and rules in each country.